P81 Effect of COVID-19 infection and preventive public health measures on haemodynamics, activity and quality of life in patients with pulmonary arterial hypertension. (11th November 2022) - Battersby, CP; Middleton, JT; Zafar, H; Binmahfooz, SK; Patel, J; Neelam-Naganathan, D; Toshner, M; Reddy, A; Lewis, R; Watson, L; Swift, A; Condliffe, R; et al.
Abstract : Introduction & Objectives: In patients with pulmonary arterial hypertension (PAH), cardiopulmonary haemodynamics and exercise capacity relates to clinical outcomes, and exercise training improves cardiopulmonary function. Public health measures that limit physical activity have been widely enforced to reduce COVID-19 transmission. COVID-19 infection causes endothelial dysfunction, which is central to the pathophysiology of PAH. Here, we describe the temporal effects of UK government restriction measures on daily activity and quality of life (QoL) in patients with PAH and the effect of COVID-19 infection on cardiopulmonary haemodynamics and physical activity. Methods: Patients were enrolled in FIT-PH (NCT04078243 ) and implanted with remote monitoring devices that provided mean pulmonary artery pressure (mPAP), cardiac output (CO; CardioMEMS, Abbott), day/night heart rate (DHR/NHR), heart rate variability (HRV), and physical activity (PA; Medtronic LinQ). Data were transmitted and reviewed in accordance with established clinical protocols. Standard questionnaires were administered remotely to assess QoL (EmPHasis-10), anxiety (GAD-7), depression (PHQ-9) and collect dates of COVID-19 infection. Results: Following a lockdown, mean activity was reduced compared to pre-lockdown levels (p<0.0001, n=26). QoL was reduced (p<0.01), whereas anxiety (p<0.001) and depression scores increased (p<0.001) compared to pre-lockdown levels. During lockdown measures, there was no change in mPAP, CO, DHR, NHR, or HRV. Of the cohort, 7 patients contracted COVID-19, leading to an decreased CO, increased mPAP and total pulmonary resistance. Consistent with observed changes in haemodynamics PA, HRV, DHR were reduced and NHR increased. Conclusions: In this cohort of patients with PAH, protective health measures resulted in reduced daily activity and QoL and were associated with increased anxiety and depression indicators. COVID-19 infection resulted in acute changes to haemodynamics and physical activity.